The Intergovernmental Alternative: ‘Tertial Law’ and Agreements Outside the Framework of Treaties - Sehnálek, David (Unequal Equals? The Status of Member States in an Integrating European Union, 2026)
In this chapter of the monograph, I will deal with the legal status of so-called subsidiary treaties concluded among EU Member States outside the framework of EU law, but with a close legal link to it. I will analyse their relationship to primary and secondary EU law, compare them to interstate compacts in the USA, and examine their nature on the basis of their interpretation by the CJEU. I will also address the question of EU and Member State competences in the context of these treaties, and the implications of the Lisbon Treaty on their existence. In particular, my analysis will focus on whether these treaties constitute a source of international or EU law. The key question is then whether these treaties represent a possible alternative to cooperation between EU Member States vis-à-vis the European Union. Finally, I will focus on the scope and future of subsidiary treaties within European integration.